2004
DOI: 10.1002/ijc.20406
|View full text |Cite
|
Sign up to set email alerts
|

Significant proportion of breast and/or ovarian cancer families of French Canadian descent harbor 1 of 5 BRCA1 and BRCA2 mutations

Abstract: In 1998, we reported that a significant proportion of breast and/or ovarian cancer families of French Canadian descent harbor specific germline mutations in BRCA1 or BRCA2 attributed to common founders. Here we report the frequency of previously described mutations (n ‫؍‬ 7) and 13 mutations identified in French Canadian families since 1998, in a new group of families (n ‫؍‬ 88). Four of the previously described mutations, 4446C>T, 2953delGTAinsC, 8765delAG and 6085C>T, account for 72% and 69% of mutation-posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
103
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 42 publications
(122 citation statements)
references
References 29 publications
(27 reference statements)
10
103
1
Order By: Relevance
“…In total, ~0.4% of the same cohort of breast cancer cases not selected for a family history of cancer, and who were also analyzed for the presence of recurrent BRCA1/BRCA2 mutations, were identified to be PALB2:c.2323C>T [p.Q775X] carriers, whereas no carriers were observed among newborns (7). These results are consistent with those of previous studies, which reported that ~40 and 1% of French Canadian breast cancer and breast-ovarian cancer families harbor germline BRCA1/BRCA2 or PALB2 germline mutations, respectively (2,3,8,9).…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…In total, ~0.4% of the same cohort of breast cancer cases not selected for a family history of cancer, and who were also analyzed for the presence of recurrent BRCA1/BRCA2 mutations, were identified to be PALB2:c.2323C>T [p.Q775X] carriers, whereas no carriers were observed among newborns (7). These results are consistent with those of previous studies, which reported that ~40 and 1% of French Canadian breast cancer and breast-ovarian cancer families harbor germline BRCA1/BRCA2 or PALB2 germline mutations, respectively (2,3,8,9).…”
Section: Introductionsupporting
confidence: 83%
“…French Canadian families with breast cancer and breast-ovarian cancer syndrome present with recurrent mutations in the BRCA1, BRCA2 or PALB2 breast cancer susceptibility genes (1)(2)(3). This has been attributed to common founders in the Quebec provincial population (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…In hereditary breast and ovarian cancer pedigrees, such recurrent mutations have been identified in BRCA1 and BRCA2 where five founder mutations account for 75-85% of all mutations present in the French Canadian population of Quebec (Oros et al, 2004;Simard et al, 2007). More recently, a single mutation in PALB2, p.Q775X, has been described as a founding mutation in French Canadian breast cancer families (Foulkes et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…About 40% of French Canadian cancer families with at least three or more cases of breast and/ovarian cancer carry a pathogenic BRCA1/2 mutation [4,[9][10][11]. Although 15 different BRCA1/2 mutations have been reported in French Canadian cancer families, five specific frameshift or nonsense mutations in BRCA1 (c.4327C[T (R1443X), c.2834_2836delGTAinsC); and BRCA2 (c.8537_8538de-lAG, c.5857G[T (E1953X), c.3167_3171delAAAAG) have been shown to account for a significant majority of mutation-positive families [9][10][11][12][13]. This has been attributed to a shared ancestry of mutation carriers due to common founders of the French Canadian population of Quebec [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%